2015
DOI: 10.1016/j.phpro.2015.08.106
|View full text |Cite
|
Sign up to set email alerts
|

Split-Spectrum Signal Processing for Reduction of the Effect of Dispersive Wave Modes in Long-range Ultrasonic Testing

Abstract: This paper presents a Split-Spectrum Signal Processing (SSP) with applications to Long Range Ultrasonic Testing (LRUT). The problem of coherent noise due to Dispersive Wave Modes (DWM) in the context of ultrasonic scattering is addressed and a novel solution by utilizing the SSP technique is proposed for reduction of the effects of DWM in the received signal. The proposed technique investigates the sensitivity of SSP performance to the filter bank parameter values such as processing/filter bandwidth, and filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…This value is the best possible compromise between the achieved defect length and the possibility of detecting false alarms. For method three, the average value is calculated using Equation (11), and minimum and maximum values are achieved by manually replacing the average in Equation (14). For both of the other methods, the average value is calculated manually from the achieved minimum and maximum values in the tests.…”
Section: Limits Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is the best possible compromise between the achieved defect length and the possibility of detecting false alarms. For method three, the average value is calculated using Equation (11), and minimum and maximum values are achieved by manually replacing the average in Equation (14). For both of the other methods, the average value is calculated manually from the achieved minimum and maximum values in the tests.…”
Section: Limits Definitionsmentioning
confidence: 99%
“…Another method for filtering the guided waves signal is the work of Pedram et al in Split-Spectrum Processing (SSP) [14,15], whereby through selecting the optimum filter parameters, the coherent noise of the test cases can be removed. However, automatic selection of the optimum filtering parameter is not possible at present.…”
Section: Introductionmentioning
confidence: 99%
“…(such as ultrasonic signal propagation speed, amplitude, etc.) in ultrasonic testing for stress experiments [48][49] . Explore the methods for correcting errors through tentative experiments, once the testing object and experimental condition change, many experiments are needed to find the method to correct the error.…”
Section: The Influence Mechanism Of Macro Factors On Ultrasonic Testimentioning
confidence: 99%
“…Modern signal processing technology can improve the reliability and accuracy of stress testing result to a certain extent. [50][51] Fig.6 (a) and (b) are Rayleigh wave signal propagating in a fixed acoustic path in Fe314 laser cladding coating under 34MPa and 230MPa tensile stress respectively [52] . It can be seen from Fig.…”
Section: The Influence Mechanism Of Macro Factors On Ultrasonic Testimentioning
confidence: 99%
“…On the other hand, other approaches have also been reported in the literature where narrowband sine waves were used as excitation sequence. Kamran et al investigated split-spectrum processing [13][14][15], where the time-domain signal is decomposed into multiple signals in different frequency bands, and then recombined in time-domain in order to remove the coherent noise. In their most recent work [15], it was reported that using the optimum filter parameters and polarity thresholding method for recombination, the SNR of defects with sizes as small as 2% cross-sectional area (CSA) could be improved significantly.…”
Section: Introductionmentioning
confidence: 99%